Kajian Yuridis Pemutusan Hubungan Kerja Oleh Perusahaan Terhadap Pekerja Yang Menolak Mutasi - Hanifah Hasna Hanifah; Khayatudin Khayatudin; Sicilya Mardian Yoel (Estudiante Law Journal, 2021)
Abstract: This study discusses the legal certainty related to Termination of Employment by the company to workers who refuse transfers which until now there is no absolute regulation, even in Law Number 13/2003 concerning Employment Law. The cases raised in this research are Study Number:53/Pdt.Sus.Phi/2018/Pn.Palu, Study Number:85/Pdt.Sus.Phi/2019/Pn/Pbr. The formulation in this research, is the act of Termination of Employment on the grounds of refusal to mutation can be justified based on the provisions of Law Number 13/2003 concerning Employment Law? And what is the basis for the judge's consideration to accept and reject the lawsuit against workers who were laid off for refusing a mutation in Study Number:53/Pdt.Sus.Phi/2018/Pn.Palu, Study Number:85/Pdt.Sus.Phi/2019/Pn /pbr? The purpose of this study is to examine how the implementation of law in Indonesia and the legal protection about termination of Industrial Relations by the company to workers who refuse mutation. To analyze the reasons for accepting and rejecting the judge's decision related to termination of employment by the company against workers who refuse to mutation with the  Study Number:53/Pdt.Sus.Phi/2018/Pn.Palu, Study Number:85/Pdt.Sus.Phi/2019/Pn/Pbr, based on Employment Law. This research is used normative method, which examines the judge's decision juridically using Law No.13/2003 concerning Employment Law. The results of this study indicate that the mutations by the company in Study Number:53/Pdt.Sus.Phi/2018/Pn.Palu and Study Number: 85/Pdt.Sus.Phi/2019/Pn/Pbr violate Article 32 of the Employment Law. because the  mutation did not pay attention to the workers' rights based on the principles of being open,free,objective,fair,and equal without discrimination.Keywords: Criminal; Replacement; Corruption;